Rethinking Censorship: A Case Study of Singaporean Media - Yuong, Siao (Javnost-The Public, 2018)
Singapore is often represented as an example of a successful “postcolonial” society that transitioned into a developed nation and economy. The government articulates its reliance on enlightenment ideals such as reason and meritocracy, separation of church and state, and equality; but at the same time draws its legitimacy from articulations of “tradition” based on “ethnicity” and “culture.” These contradictions extend to censorship, particularly since the state actively censors the media when it comes to issues of race and religion whenever they threaten to disrupt the appearance of equality, while selectively using repackaged “Asian values” to justify their interventions. To convolute matters further, critics and academics often employ quasi-Western concepts of “freedom of expression” to critique state censorship. So, what underlying assumptions do these various representations articulate? And how do these rival articulations relate to the ways censorship work in practice? Drawing on ethnographic materials obtained during an intensive 15-month fieldwork conducted between 2012 and 2013, this article aims to complicate dominant conceptualisations of censorship by shifting its focus onto situated practices.